The shaping of covert social networks: isolating the effects of secrecy - Fielding, Nigel (Trends in organized crime, 2017)
Secrecy amongst participants is widely regarded as a hallmark of organized crime. Accordingly, covertness is treated as an essential feature of organized crime networks and as one of the distinctive characteristics differentiating such networks from others. In other respects contemporary understandings of organized crime networks based on routine activities theory see strong parallels between criminal organizations and legitimate business organizations. Noting the scarcity of empirical evidence about covert networks and flaws in the conceptualization of how such networks form and operate, this article questions the basis for the assumption that covertness is a distinctive feature of organized crime networks.